ANALISIS HUKUM NATURALISASI KEWARGANEGARAAN INDONESIA DALAM SEPAK BOLA : STUDI KASUS NENEK IVAR (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This article examines the development of athlete naturalization regulations in Indonesia, highlighting the case of Ivar Jenner, who has lineage from Jember, as a concrete example of the mechanism for granting citizenship status to foreign athletes. The study employs a normative juridical approach, utilizing data analysis through literature review encompassing laws, government regulations, court decisions, as well as scientific literature and news articles, aiming to understand the legal basis and policies behind the athlete naturalization process, particularly in football. The analysis reveals a fundamental difference between general naturalization regulations, which emphasize strict administrative requirements, and special athlete policies designed to simplify procedures to support the improvement of the national team's achievements. Comparative studies with practices in other countries, such as South Korea, show that Indonesia’s naturalization mechanism has been adapted according to national cultural and legal contexts. Although athlete naturalization has proven to positively impact the enhancement of the national team’s performance and serves as an inspiration for young players, the policy also raises debates regarding fairness, legality, and national identity. The article’s findings emphasize the need for intensive coordination among stakeholders to overcome administrative obstacles and refine the naturalization mechanism, so that the policy does not hinder the development of local athletes while still supporting the construction of citizenship identity in the globalization era.Keywords: Naturalization, Athletes, Regulation, Law, National Identity ABSTRAK.Artikel ini mengkaji perkembangan regulasi naturalisasi atlet di Indonesia dengan menyoroti kasus Ivar Jenner yang memiliki garis keturunan dari Jember sebagai contoh konkret mekanisme pemberian status warga negara kepada atlet asing. Studi yang menggunakan pendekatan yuridis normatif ini memanfaatkan analisis data melalui studi kepustakaan yang mencakup undang-undang, peraturan pemerintah, putusan pengadilan, serta literatur ilmiah dan artikel berita, dengan tujuan memahami dasar hukum dan kebijakan di balik proses naturalisasi atlet, khususnya dalam ranah sepak bola. Hasil analisis mengungkap perbedaan mendasar antara regulasi naturalisasi umum yang menekankan syarat administratif ketat dengan kebijakan khusus atlet yang dirancang untuk menyederhanakan prosedur demi mendukung peningkatan prestasi tim nasional. Studi perbandingan dengan praktik di negara lain, misalnya Korea Selatan, menunjukkan bahwa mekanisme naturalisasi di Indonesia telah diadaptasi sesuai dengan konteks budaya dan hukum nasional. Meski naturalisasi atlet terbukti memberikan dampak positif terhadap peningkatan performa tim nasional serta berperan sebagai inspirasi bagi pemain muda, kebijakan tersebut juga menimbulkan perdebatan terkait keadilan, legalitas, dan identitas nasional. Temuan artikel menekankan perlunya koordinasi intens antar pemangku kepentingan untuk mengatasi kendala administrasi dan mempertajam mekanisme naturalisasi, sehingga kebijakan tersebut tidak menghambat pengembangan atlet lokal serta tetap mendukung pembangunan identitas kewarganegaraan di era globalisasi.Kata Kunci: Naturalisasi, Atlet, Regulasi, Hukum, Identitas Nasional